FENOMENA MASA DEPAN HUTAN DALAM KARYA LUKIS SUREALIS - RAMON SYAPUTRA, Drs. Nurzal Zai, Drs. Abd. Hafiz, M.Pd (Serupa The Journal of Art Education, 2014)
Widespread destruction of forests such as combustion, can damageecosystems and human health. Public awareness should also grown to love theforest by way of keeping, caring for and preserving and maintaining the balanceof the human relationship with nature in order to create a harmonious life . Toexpress these events, the authors learns various phenomena of forest destructionin Indonesia through various media such as television, newspapers, books, andthrough observation of dry trees without leaves, barren and arid forests are locatedaround the writer’s residence. The main purpose of this final project is to provide insight on the importance of forest conservation community that provides manybenefits for life.Key word: Phenomena